Spondylitis/spondylodiscitis - Ahlhelm, F; Kelm, J; Naumann, N; Shariat, K; Grunwald, I; Reith, W; Nabhan, A (2006)
Spondylitis is an inflammation of the vertebral body. If the infection is manifested in the vertebral motor segment it is called spondylodiscitis, which can be divided into specific and nonspecific forms. It is clinically impressive that at the beginning of the disease, the patients who are quite often immunosuppressed suffer from localized, especially nocturnally exacerbated backache. The initial diagnostic work-up generally consists of clinical history, examination, laboratory tests, and (especially advanced) imaging findings. Although computed tomography still remains the most frequently used advanced imaging technique, magnetic resonance imaging is the golden standard for the diagnosis of spondylitis and spondylodiscitis. © Springer Medizin Verlag 2006.